2012
DOI: 10.1039/c2em10826g
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal source influence on river mass flows of benzotriazoles

Abstract: The anticorrosive agents 1H-benzotriazole (1H-BT), 4-methyl-1H-benzotriazole (4 Me-BT) and 5-methyl-1H-benzotriazole (5 Me-BT), which are usually added to dishwasher detergents, automotive antifreeze formulations and aircraft de-icing/anti-icing fluids (ADAFs), were measured in river water. Samples were collected from 15 sampling sites in the mainstream and selected tributaries of a medium-sized catchment area during summer and winter periods. The aim of this study was to assess a seasonal source influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 21 publications
4
25
0
Order By: Relevance
“…BZT inputs to watersheds in the Greater Toronto Area track salt inputs nearly perfectly, and both can peak in spring and fall thaws (Parajulee et al., ). Sites with high input and little flow‐through may be most likely to reach stressfully high concentrations, such as ponds near snow storage sites (Alvey et al., ), airfields (Breedveld et al., ), or dense road areas (Kiss and Fries, ; Parajulee et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…BZT inputs to watersheds in the Greater Toronto Area track salt inputs nearly perfectly, and both can peak in spring and fall thaws (Parajulee et al., ). Sites with high input and little flow‐through may be most likely to reach stressfully high concentrations, such as ponds near snow storage sites (Alvey et al., ), airfields (Breedveld et al., ), or dense road areas (Kiss and Fries, ; Parajulee et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…BTRs consist of a benzene ring fused with a triazole ring, they are soluble in water, slightly basic (pK a 8.2-8.8) and have a weak tendency to sorb onto organic matter (Weiss et al, 2006). They are widely used in several industrial applications for protection of metal mechanical parts, as well as in everyday products and dishwashing detergents (Janna et al, 2011;Kiss and Fries, 2012). In the case of BTHs, a benzene ring is fused with a thiazole ring.…”
Section: Introductionmentioning
confidence: 99%
“…According to their relatively low degradability (Pitter and Chudoba 1990), BT is commonly emitted into rivers by waste water effluents . On account of their low sorption capacity (Hart et al 2004), BTs occur mostly in the aquatic environment Kiss and Fries 2009;Reemtsma et al 2010;Janna et al 2011;Kiss and Fries 2012). However, the mobility of these polar compounds in the environment is still not well characterized, although their presence in ground water (Cancilla et al 1998;Hollender 2007), bank filtrate (Reemtsma et al 2010), and drinking water have already been reported (van Leerdam et al 2009).…”
Section: Benzotriazoles and Benzothiazolesmentioning
confidence: 93%